Perancangan Decoupling Control System Suhu dan Kelembapan Menggunakan Metode Kontrol PID pada Mesin Pengering Krupuk Tipe Trush Burner - Basruqi, Basruqi; Basri, Muhammad Hasan (Rekayasa, 2021)
Crackers are one of the traditional foods in Indonesia which now has many home industries to produce it. There are 3 ways of drying, including traditional, modern, and hybrid. In the study of designing a temperature and humidity control system using the PID method on a trush burner cracker dryer, it was carried out in a modern way, with the materials needed for design, plastic waste, Arduino Uno, DHT11 sensor, oven, boiler, and pump. From the test results, the maximum water pipe testing was carried out at a temperature of 53 oC, the maximum drying room temperature was 45 oC, and the maximum boiler temperature was 56 oC. The function of the temperature and humidity control system on the trush burner type cracker dryer helps dry crackers practically in rainy season conditions